Pengaruh Konsentrasi Ragi Rhizopus oligosporus DP02 Bali Terhadap Karakteristik Tempe Kacang Hijau (Vigna radiata, L.) - Izzah, Karimatul; Duniaji, Agus Selamet; Ayu Ekawati, I Gusti (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2023)
The research was conducted with the aims to determine the effect of yeast concentration with Rhizopus oligosporus DP02 Bali on the characteristics of green bean tempeh and to determine the righ yeast concentration to produce green bean tempeh with the best characteristic. The research used completely randomized design with yeast concentration consisting of 5 different levels as the treatment, namely 1%, 1,5%, 2%, 2,5%, and 3%. Each levels was repeated 3 times to obtain 15 experimental units. The data were analyzed using ANOVA, and if there was a significant effect, the Duncan Multiple Range Test were perfomed. The results showed that the treatment had a significant effect on the green bean tempeh water content, ash content, protein content, fat content, carbohydrate content, curd fiber content, aroma, taste, texture, color, and overall acceptance. Yeast concentration of 3% produced the green bean tempeh with the best characteristics with water content of 54.17%, ash content of 0.60% , protein content of 8.22%, fat content of 2.53%, carbohydrate content of 33.79%, curd fiber content of 9.48%, and characteristics of color was liked, taste was liked, texture was liked, and overall acceptance was liked.